(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The two-day community service activity by PPKn students from Sembilanbelas November University, Kolaka, in Rano Jaya Village aims to increase community participation in routine health checks through Posyandu and Posbindu. The research method used Participatory Action Research (PAR) with 68 participants, including toddlers, pregnant women, the elderly, Posyandu cadres, Posbindu administrators, medical personnel, and students. Data were collected through observation, interviews, and documentation, then analyzed qualitatively using content analysis techniques. The results showed an increase in community participation from 48% to 85%, increased awareness of the importance of health checks and early disease detection, and strengthened the capacity of health cadres. This activity also fostered a spirit of mutual cooperation and strengthened social solidarity, proving the application of Pancasila values effectively in strengthening community health participation that is healthy, empowered, and imbued with a sense of togetherness.